Directly sputtered nickel electrodes for alkaline water electrolysis. (1st August 2021) - Han, Won-Bi; Kim, Ik-Sun; Kim, MinJoong; Cho, Won Chul; Kim, Sang-Kyung; Joo, Jong Hoon; Lee, Young-Woo; Cho, Younghyun; Cho, Hyun-Seok; Kim, Chang-Hee
Highlights: DC- and RF-sputtered Ni electrodes were prepared for the catalyst of hydrogen evolution reaction. Sputtered Ni electrodes showed better performance in electrochemical activity, compared with that of the conventional Raney Ni electrode. In-situ single cell test station results exhibited high long-term stability and on/off durability for two weeks. Abstract: Hydrogen is regarded as a highly clean and renewable future energy resource. Water electrolysis (WE) is the most promising technology to produce hydrogen at large scale without carbon dioxide generation. In this study, we prepared Ni electrodes for alkaline water electrolysis purpose using various methods, including direct sputtering (DC and RF operational modes) and the Raney Ni process, and investigated their morphologies and electrochemical activities in the hydrogen evolution reaction (HER). The DC-sputtered Ni electrode showed well-controlled surface morphology with around 40-fold roughness enhancement, compared to the Ni substrate. Half-cell HER test showed that DC-sputtered Ni electrode provides the best electrochemical performance, including the lowest overpotential of 100 mV at a current density of 50 mA/cm 2, and provides the lowest Tafel slope, representing the fastest charge transfer reaction and kinetics of HER. More importantly, for practical application purposes, single-cell test was also conducted to confirm the on/off durability and long-term stability, which showed highly stable electrochemical activity under harsh operational conditions. We expect that our approach will launch a new trajectory for realizing CO2 -free, cost-effective, and scalable hydrogen production for industrial application purpose, even in combination with renewable power sources, including solar, wind, and hydro energy. Graphical abstract: Image, graphical abstract